Self-Interest Induces Counter- Empathy at the Late Stage of Empathic Responses to Others’ Economic Payoffs - Jie, Jing; Luo, Pinchao; Zhuang, Mengdi; Li, Beibei; Pang, Yu; Li, Junjiao; Zheng, Xifu (Frontiers in Psychology, 2019)
Previous studies have found that individuals exhibit empathic responses when others are treated unfairly. However, there remains a lack of clarity over the extent to which self-interest regulates these empathic responses, and in identifying which component of empathy is more likely to be affected. To investigate these issues, an experiment was designed based on a money distribution task with two conditions (observation vs. participation), and carried out using scalp-recorded event-related potentials (ERPs). Behavioral data showed that the participants’ empathic responses were consistent with their coplayers’ emotional expressions in the observation condition, whereas they were inconsistent with the coplayers’ expressions in the participation condition. The electrophysiological data showed that the neural encoding of facial expressions (reflected in the N170) was not affected by self-interest. However, the late stage of empathic responses (LPP) showed a decline when participants’ self-interest was involved. Disadvantageous inequality and relatively fair distribution to others elicited a more pronounced feedback-related negativity (FRN) than advantageous inequality distribution in both the observation and participation conditions. As the late stage of empathic responses is also indexed by the LPP amplitude, these results indicate that the participants were more concerned for their own outcomes than for others’ benefits when self-interest was involved, which reduced their empathy towards their coplayers at the late stage of empathic responses.